FDI, development and the multilateral investment framework - Samuel, Lacombe (Department of Commercial Law, 2023)
The internationalization of production and consumption has been the defining feature of the world economy since the mid 1980's. Foreign direct investment (FDI), broadly defined as the creation of enterprises abroad or the acquisition of substantial stakes in existing enterprises, now represents a major form of cross border capital flow. More than ever firms and industries in many more countries are expanding abroad through direct investment. It has been estimated that today worldwide some 65000 Multinational enterprises (MNEs), have established more than 850 000 foreign affiliates. Foreign affiliates now account for about one third of world exports.